Long-lasting renewable antibacterial N-halamine coating enable dental unit waterlines to prevention and control of contamination of dental treatment water - Xing, Min; Zhang, Haifeng; Li, Zhiyao; Zhang, Ling; Qian, Wenhao (Frontiers in Materials, 2024)
Developing bacterial biofilm on the dental unit waterlines increases the risk of cross-infection among oral patients. Although chemical disinfectants can achieve disinfection effects in a short period of time, corrosion damage of dental unit waterlines and water contamination can also occur after continuous use of it. Herein, this study explored a one-step deposition method to prepare a durable and renewable antibacterial N-halamine polymeric coating on polyurethane waterlines. The method utilized polyelectrolyte complexes formed with polyethylenimine (PEI) and phytic acid (PA), followed by chlorination to activate the antibacterial properties. The N-halamine polymeric coating reduces the polyurethane waterline's water contact angle, thus reducing biofouling deposits and the obstruction of the active halide site on the waterlines, thereby facilitating the maintenance of the cleanliness of the coating. In addition, benefiting both from the active chlorine release and the high density of positive charges on the coating, the polyurethane waterline antimicrobial activity is significantly enhanced. Besides, the N-halamine polymeric coating is biocompatible. This study showed that long-lasting and renewable antimicrobial requirements can be achieved by simple surface modification of N-halamine polymer coatings, which provides a practicable strategy for the production of long-term and reproducible antibacterial dental unit waterlines to reduce the incidence of hospital infection in oral department.